2022
DOI: 10.1177/17588359221107111
|View full text |Cite
|
Sign up to set email alerts
|

Lobaplatin-based neoadjuvant chemotherapy for triple-negative breast cancer: a 5-year follow-up of a randomized, open-label, phase II trial

Abstract: Purpose: We report the 5-year follow-up findings of a randomized, open-label, phase II trial of lobaplatin-based neoadjuvant chemotherapy plus adjuvant therapy for triple-negative breast cancer (TNBC). Patients and methods: This study included patients aged ⩾18 years with untreated, operable stage I–III TNBC and an Eastern Cooperative Oncology Group performance status of 0 or 1. One group of patients (TE group, n = 99) received four cycles of docetaxel (T, 75 mg/m²) plus epirubicin (E, 80 mg/m²) every 3 weeks,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…This is expected to be the case in our current practice as well, although the current data is immature, and long-term follow-up is needed. As for toxicity, in combination with the results of the current study and two previous studies conducted by our team on lobaplatin, we hypothesize that, compared to the regimen of taxane plus anthracycline, the TL regimen increases the risk of grade-3/4 anemia, but decreases the risk of grade-3/4 neutropenia [8,9]. There are some limitations to this clinical trial.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…This is expected to be the case in our current practice as well, although the current data is immature, and long-term follow-up is needed. As for toxicity, in combination with the results of the current study and two previous studies conducted by our team on lobaplatin, we hypothesize that, compared to the regimen of taxane plus anthracycline, the TL regimen increases the risk of grade-3/4 anemia, but decreases the risk of grade-3/4 neutropenia [8,9]. There are some limitations to this clinical trial.…”
Section: Discussionmentioning
confidence: 54%
“…As we previously reported in a phase-II clinical trial and 5-year follow-up study, the addition of lobaplatin to taxane and anthracycline was found to significantly improve overall pathologic and objective response rates and DFS. [8,9]. A phase II study compared the efficacy and toxicity of TL (docetaxel + lobaplatin) induction chemotherapy combined with lobaplatin concurrent chemoradiotherapy and TPF (docetaxel + cisplatin + 5-fluorouracil) induction chemotherapy combined with cisplatin concurrent chemoradiotherapy in the treatment of locally advanced head and neck squamous cell carcinoma, and the results indicated that patients survived longer and experienced lower toxicity when treated with TL regimen [10].…”
Section: Introductionmentioning
confidence: 99%
“…Lobaplatin (LBP), a third-generation platinum-based drug only available in the Chinese market, has been approved for treating metastatic BC, chronic granulocytic leukemia, and small cell lung cancer ( 5 ), for which surgical removal is not an option. In addition, some studies have confirmed that LBP is effective in treating other cancer types, including cervical cancer, triple-negative breast cancer, primary hepatocellular carcinoma, and T4 gastric cancer ( 6 - 9 ). Compared to other platinum-based chemotherapy drugs on the market, such as cisplatin (DDP), LBP is less toxic to the kidney, nerves and ear and bypasses the DDP resistance of cancer cells ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“… 6 In addition, a phase II randomized controlled clinical study of our group showed that neoadjuvant therapy with LBP can improve the pCR and ORR rates of TNBC, with tolerable side effects and a trend towards improving long-term survival. 7 , 8 …”
Section: Introductionmentioning
confidence: 99%